2015
DOI: 10.1021/jo502732y
|View full text |Cite
|
Sign up to set email alerts
|

Understanding “On-Water” Catalysis of Organic Reactions. Effects of H+ and Li+ Ions in the Aqueous Phase and Nonreacting Competitor H-Bond Acceptors in the Organic Phase: On H2O versus on D2O for Huisgen Cycloadditions

Abstract: For a typical Huisgen cycloaddition, carried out on water, the behavior of water molecules at the oil-water interface depended on the properties of the reactants. With weakly basic reactants, a small quantity of added H(+) (HClO4, 0.0001-0.01 M) present in the aqueous phase had negligible effects, but larger quantities of H(+) (HClO4, 0.1-3.0 M) increased the catalytic effect and caused protons to cross the water-organic interface and affect the products. Added Li(+) ions (LiClO4, 0.1-3.0 M) had no effect for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 43 publications
1
32
1
Order By: Relevance
“…For the Diels–Alder reaction of methyl acrylate ( A ) with cyclopentadiene ( B ), this novel reaction medium provides large rate enhancements of up to 10 6 to 10 8 times with the values of the rate constants ranging from 80.6 to 1990 s −1 , and high endo / exo values ranging from 2.8 to 8.0, as compared to homogeneous media (Scheme ). Both the rate constants as well as the stereoselectivity for interfacial reactions were noted to be exceedingly larger than previously reported values for the same reaction at the given concentrations, in conventional solvent media, including water …”
Section: Methodscontrasting
confidence: 73%
See 4 more Smart Citations
“…For the Diels–Alder reaction of methyl acrylate ( A ) with cyclopentadiene ( B ), this novel reaction medium provides large rate enhancements of up to 10 6 to 10 8 times with the values of the rate constants ranging from 80.6 to 1990 s −1 , and high endo / exo values ranging from 2.8 to 8.0, as compared to homogeneous media (Scheme ). Both the rate constants as well as the stereoselectivity for interfacial reactions were noted to be exceedingly larger than previously reported values for the same reaction at the given concentrations, in conventional solvent media, including water …”
Section: Methodscontrasting
confidence: 73%
“…The importance of heterogeneous reaction media to achieve large rate enhancements for Diels–Alder reaction under ′on water′ conditions was further highlighted by Klijn and Engberts . Butler and Coyne have reported that reactants with different solubilities in water display different rates for Huisgen cycloadditions reactions . A theoretical study from Jung and Marcus described the catalyzing effects of trans ‐phase dangling of OH groups to increase the rates of ′on water′ organic reactions .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations